2003
DOI: 10.1034/j.1600-0714.2003.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and distribution of myoepithelial cells during atrophy of the rat sublingual gland

Abstract: The observations suggest that the distribution of myoepithelial cells change during atrophy of rat sublingual glands and that myoepithelial cells have low proliferative activity in both the normal and atrophic condition of rat sublingual glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
2
18
2
Order By: Relevance
“…It has been also reported that myoepithelial cells in the atrophy of sublingual glands do not proliferate actively and that their proliferative activity maintains the level of the controls during atrophy (Takahashi et al 2003). These facts suggest that the proliferative activity of myoepithelial cells in the sublingual gland is unchanged and stays low under a variety of pathological circumstances.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It has been also reported that myoepithelial cells in the atrophy of sublingual glands do not proliferate actively and that their proliferative activity maintains the level of the controls during atrophy (Takahashi et al 2003). These facts suggest that the proliferative activity of myoepithelial cells in the sublingual gland is unchanged and stays low under a variety of pathological circumstances.…”
Section: Discussionmentioning
confidence: 57%
“…Since myoepithelial cells participate in the histogenesis of several kinds of salivary gland tumors (Batsakis et al 1983, Dardick & Nostrand 1987, Redman 1994, it is possible to consider that the differences in proliferative activity of myoepithelial cells among the three major salivary glands are related to the differences in the frequencies and in the types of tumors of the salivary glands developing in the three glands. It has been speculated that the differences in the proliferative activity of myoepithelial cells originate in different distributions of myoepithelial cells (Takahashi et al 2001(Takahashi et al , 2004b or in different mechanisms of acinar cell deletion in the gland atrophy (Takahashi et al 2003). However, these two hypotheses are insufficient to explain the differences fully and there may be additional factors.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Salivary glands with ligated ducts show signs of inflammation, edema, and death of the acinar cells 85–89. When the duct ligation is released, the salivary glands go through a process of repair through proliferation of acinar, ductal, and/or myoepithelial cells 86,88,9094. Similarly, studies on the pancreas,9597 liver,98,99 intestine,100 and mammary glands101 reported self-regenerating capabilities of these tissues.…”
Section: Injury and Repair Of The Lacrimal Glandmentioning
confidence: 98%
“…19 -24 In particular, the regenerative capacity of the salivary glands has been well documented. 22,23,[25][26][27][28][29][30] Long-term (7-21 days) ligation of the main excretory ducts of the salivary glands leads to atrophy of the glands. The ligation of the salivary gland corresponds with inflammation, edema, and death of acinar cells.…”
mentioning
confidence: 99%